2005
DOI: 10.1080/10715760500177500
|View full text |Cite
|
Sign up to set email alerts
|

Relation between oxidative stress markers and antioxidant endogenous defences during exhaustive exercise

Abstract: Hydrogen peroxide (H2O2) could induce oxidative damage at long distance from its generation site and it is also an important signalling molecule that induces some genes related to oxidative stress. Our objective was to study the plasma and blood cells capability to detoxify H2O2 after intense exercise and its correlation with oxidative damage. Blood samples were taken from nine professional cycling, participating in a mountain stage, under basal conditions and 3 h after the competition. Catalase and glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
106
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 43 publications
12
106
0
9
Order By: Relevance
“…34,35 In this study, we report an increase of TBARS, NPSH, and ascorbic acid levels in skeletal muscle of mice 1 h after continuous swimming exercise. Moreover, 24 h after physical exercise, TBARS and ascorbic acid levels remained increased in skeletal muscle of mice.…”
Section: Discussionsupporting
confidence: 50%
“…34,35 In this study, we report an increase of TBARS, NPSH, and ascorbic acid levels in skeletal muscle of mice 1 h after continuous swimming exercise. Moreover, 24 h after physical exercise, TBARS and ascorbic acid levels remained increased in skeletal muscle of mice.…”
Section: Discussionsupporting
confidence: 50%
“…Based on studies that have measured redox homeostasis in tissues other than blood and skeletal muscle, it is certain that acute exercise alters redox homeostasis in practically every fluid, blood cell, tissue and organ. In fact, several studies have found alterations in redox homeostasis after acute exercise in exhaled breath (Mercken et al, 2005), urine (McAnulty et al, 2010), lymphocytes (Boudreau et al, 2005), neutrophils (Sureda et al, 2005), diaphragm (Itoh et al, 2004), heart (Nie et al, 2010), liver (Liu et al, 2000), lung (Prigol et al, 2009), spleen (Kruger et al, 2009), thymus , kidney (Leeuwenburgh and Ji, 1995) and brain (Lappalainen et al, 2010). This is not to imply that all tissues respond both qualitatively and quantitatively in a similar way to the same exercise stimulus.…”
Section: Effects Of Very Short Duration Exercise On Redox Homeostasismentioning
confidence: 90%
“…Some production of RONS is necessary for normal contractile activity of skeletal muscles [72,144], and physical training is a known to induce antioxidant enzymes [44,61]. However, strenuous exercise, mainly if above habitual intensity of effort, or training with very elevated frequency, generally overloads the endogenous antioxidant system's capacity, leading to an increase in plasma lipid peroxidation [44] plus oxidative damage to muscles and other tissues [44,61,128,132]. These damaging effects, with their consequent inflammatory processes, can jeopardize performance and may lead to overtraining syndrome, besides potentially contributing to an increased future risk of cardiovascular disease (CVD) [37,44,109,131,136].…”
Section: Introductionmentioning
confidence: 99%
“…Many athletes and individuals participating in regular exercise programs consume antioxidant supplements to avoid enhanced production of reactive oxygen and nitrogen species (RONS) in response to exercise, which may lead to modifications in lipids, proteins, nucleic acid, and other cellular compounds due to oxidative stress [37,44,109,128,144]. Some production of RONS is necessary for normal contractile activity of skeletal muscles [72,144], and physical training is a known to induce antioxidant enzymes [44,61].…”
Section: Introductionmentioning
confidence: 99%